2022
DOI: 10.2169/internalmedicine.7990-21
|View full text |Cite
|
Sign up to set email alerts
|

Severe Asthma Where Eosinophilic Granulomatosis with Polyangiitis Became Apparent after the Discontinuation of Dupilumab

Abstract: The use of biologic agents has enabled control of severe asthma, but there is a risk that eosinophilic granulomatosis with polyangiitis (EGPA) may be masked in some cases. We herein report a 71-year-old man who was administered dupilumab for 2 years to stabilize his asthma symptoms. A few months after discontinuation of dupilumab administration, an increase in the eosinophil count in peripheral blood, leg pain, and a rash appeared. Based on pathology, he was diagnosed with EGPA. EGPA in this case was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Isolated cases of chronic eosinophilic pneumonia [70][71][72], eosinophilic gastritis, [73], and eosinophilic vasculitis [74] have been associated with dupilumab in patients with asthma. Therefore, dupilumab could be considered as being directly related to or unmasking previous vasculitis by discontinuation or reduction of corticosteroids in asthma patients, as reported by Ikeda et al [75] and Murag et al [76]. Importantly, cases reported by Eger et al [77] highlight the importance of considering the blood eosinophil count in asthmatics who switch from an anti-IL-5/5Ra agent to an anti-IL-4/13 agent.…”
Section: Symptomatic Hypereosinophilia Induced By Dupilumab: Case Rep...mentioning
confidence: 97%
See 1 more Smart Citation
“…Isolated cases of chronic eosinophilic pneumonia [70][71][72], eosinophilic gastritis, [73], and eosinophilic vasculitis [74] have been associated with dupilumab in patients with asthma. Therefore, dupilumab could be considered as being directly related to or unmasking previous vasculitis by discontinuation or reduction of corticosteroids in asthma patients, as reported by Ikeda et al [75] and Murag et al [76]. Importantly, cases reported by Eger et al [77] highlight the importance of considering the blood eosinophil count in asthmatics who switch from an anti-IL-5/5Ra agent to an anti-IL-4/13 agent.…”
Section: Symptomatic Hypereosinophilia Induced By Dupilumab: Case Rep...mentioning
confidence: 97%
“…Given that EGPA can appear during tapering and discontinuation of systemic corticosteroids, systemic corticosteroids may be masking vasculitis [75,76,83].…”
Section: Egpa In Pivotal Studies On Asthma and Crswnp Treated With Du...mentioning
confidence: 99%
“…On the contrary, a case by Adachi et al showed that treatment with dupilumab reduced symptoms caused by EGPA such as leg edema, abdominal pain, and dyspnea [7]. Another case by Ikeda et al included a patient who presented with EGPA only after discontinuing dupilumab [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another case by Ikeda et al. included a patient who presented with EGPA only after discontinuing dupilumab [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients who developed eosinophilic disorders after dupilumab initiation had a clinical history suggestive of systemic eosinophilic disease or received several cycles of SCS tapering prior to an adverse event 8 . Some patients developed EGPA after dupilumab discontinuation or after switching biologics from anti-IL-5 or anti-IL-5 receptor alpha antibodies to dupilumab 9,10 . In our case, the development of EGPA-related symptoms and the re-elevation of ANCA were observed without a history of SCS tapering after dupilumab initiation.…”
Section: Discussionmentioning
confidence: 99%